La imagen como testimonio: paisajes visuales de la violencia en la Toma del Palacio de Justicia en 1985, en Bogotá (Colombia) - Juan Sebastián Granada-Cardona (Caravelle)
In this article, I propose an analysis of the witness’s image, based on the case of a graphic novel (Los Once) dealing with the Palace of Justice’s taking in Bogotá in 1985. The discussion that I present here aims to broaden the limits of the idea of testimony for social sciences, while highlighting certain porosities of a notion that crosses various fields, and which appears in the clash between testimonial genre and graphic fiction.